Synergistic Formulation and Activity of Earthworm-Aloe Gel for Bruise Healing : An In Vivo Study in a Murine Model - Mercya, Yovita; Oktavia Lauda; Ana Ratnasih; Whisnu Trie Seno Ajie (Universitas Muhammadiyah Malang, 2026)
Bruise is a common soft tissue injury characterized by prolonged inflammation and fibrin deposition. Topical heparin sodium demonstrates limited efficacy and potential side effects, warranting exploration of natural alternatives. This study formulated and evaluated a combination gel of earthworm powder (Lumbricus rubellus) and Aloe vera for topical bruise treatment. An experimental post-test only control group design was employed. Phase I involved formulation and physical evaluation of earthworm powder 5% (GEL-E), Aloe vera 100% (GEL-A), and combination gel (GEL-C). Phase II assessed in vivo efficacy using 25 male BALB/c mice (Mus musculus), aged 8–12 weeks (n=5/group), with cupping-induced bruise (1.5 cm, 60 kPa, 10 minutes). Bruise area was measured using WoundGenius® (H0–H12). Kruskal-Wallis and Mann-Whitney U tests were applied (α=0.05). All formulations met pharmaceutical specifications (CV <10%). GEL-C achieved the fastest healing (7.2 ± 1.10 days) versus GEL-E (7.6 days), GEL-A (8.8 days), heparin (8.6 days), and negative control (10.0 days), with significant differences at H3–H5 (p=0.008–0.043). GEL-C reduced healing time by 28% versus negative control and 16% versus heparin. The combination gel demonstrated a pharmacologically complementary effect and represents a promising topical alternative; however, clinical translation requires further pharmacokinetic evaluation and controlled human studies.